A preliminary study on treatment of human breast cancer xenografts with a cocktail of paclitaxel, doxorubicin, and 131I-anti-epithelial cell adhesion molecule (9C4) - Ali, Naiim S.; Akudugu, John M.; Howell, Roger W. (World Journal of Nuclear Medicine, 2019)
Triple-negative breast cancer often has devastating outcomes and treatment options remain limited. Therefore, different treatment combinations are worthy of testing. The efficacy of a cocktail of paclitaxel, doxorubicin, and 131I-anti-epithelial cell adhesion molecule (EpCAM) (9C4) to treat breast cancer was tested. Efficacy was tested with an MDA-MB-231 human breast cancer xenograft model. Anti-EpCAM (9C4) was demonstrated to bind to MDA-MB-231 human adenocarcinoma cells in vitro. Subsequently, mice-bearing MDA-MB-231× enografts were treated with either 131I-anti-EpCAM (9C4), unlabeled anti-EpCAM (9C4), paclitaxel, doxorubicin, or a cocktail of all of the agents. Tumor volume was measured for up to 70-day postinjection. Exponential regression was performed on tumor growth curves for each of the therapy groups. Statistical comparison of the growth constants λ of the regression models for each of the treatment groups with that of the cold antibody and control groups was done using extra sum-of-square F-tests. Biexponential clearance of 131I-anti-EpCAM (9C4) was observed with biological clearance half-times of 1.14 and 17.6 days for the first and second components, respectively. The mean growth rate of the tumors in animals treated with a cocktail of all of the agents was slower than in those treated with unlabeled anti-EpCAM (9C4) (P = 0.022). These preliminary data suggest that a cocktail of 131I-anti-EpCAM (9C4), paclitaxel, and doxorubicin may be suitable for treating breast cancers with high expression of EpCAM.
Keywords: Chemotherapy; doxorubicin; epithelial cell adhesion molecule; iodine-131; monoclonal antibody; paclitaxel; radioimmunotherapy